Associations between Indoor Environmental Quality and Infectious Diseases Knowledge, Beliefs, and Practices of Hotel Workers in Wuhan, China - Wang, Wenjing (Int J Environ Res Public Health, 2021)
Knowledge, beliefs, and practices regarding infectious diseases are key elements that ensure practitioners’ health and safety. It is important to carry out such a survey in hotels. This study aims to determine the levels of knowledge, beliefs, and practices regarding infectious diseases among practitioners and their associations with the environmental quality of hotels in Wuhan, China. We surveyed infectious disease knowledge, beliefs, and practices of practitioners in 18 hotels and detected these hotels’ environment, including physical factors of temperature, humidity, noise, and the indoor air quality of benzene, toluene, xylene, formaldehyde, CO, CO(2), the total count of fungi, aerobic plate count, PM(10), and PM(2.5). 128 practitioners were included, and 28.9% were male. The questionnaire included knowledge, beliefs, and practices regarding infectious diseases. Our study found moderate levels of knowledge and beliefs, and good health practices. People’s beliefs toward COVID-19 were correlated significantly with their knowledge (p < 0.05). Beliefs and health practices were correlated significantly with environmental quality (p < 0.05). However, the environmental quality was correlated negatively with the classification of hotels. Conclusively, despite the good health practices of practitioners, the knowledge and beliefs toward infectious diseases need to strengthen. Hotels should emphasize health education in practitioners and the improvement of environmental hygiene. Integrating all three components into a comprehensive environmental promotion program is warranted.